Aplikasi Lean Manufacturing System Berbasis Value Stream Mapping Pada Industri Otomotif - Aprilia Andeyu; Muhammad Aldi Albana; Fibi Eko Putra (DPPM Universitas Pelita Bangsa, 2022)
The manufacturing industry competes in improving product quality and productivity by minimizing production costs. System changes directly or indirectly include machines, materials, people, methods, and the environment by adopting lean concepts. This Value Stream Mapping method aims to focus on improvement and waste areas, especially in the production process of painting the 15 k seat cowl product. The results of this study show that the implementation of Future State Mapping can help reduce the following: production lead time decreased by 58.9%, total cycle time decreased by 7.08% and total non-value added decreased by 7.12 %. This proves that adopting the Value Stream Mapping method can make significant improvements. Keywords: Lean Manufacturing System, Value Stream Mapping, Waste